(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The article provides a comprehensive description of the concepts of “concept” and “language picture of the world”; an attempt is made to find out how concepts reflect lingua-specific features of mentality; specific features of the structure of color concepts are revealed. The main approaches to the study of color vocabulary are analyzed, including cognitive, linguacultural and psycholinguistic aspects. Particular attention is paid to the role of color in the formation of the linguistic picture of the world, the reflection of cultural values and the influence on cognitive processes. Various theories are considered that explain the universality and specificity of color designations in different languages and cultures. The problem of color designations is constantly under the close attention of many domestic and foreign linguists who used various approaches in its study. Color names were studied from the point of view of their etymology and historical development, systems approach, symbolism, semantic structure, using psycho- and ethnopsycholinguistic approaches. A number of researchers have examined names with color meanings in terms of comparison, studied the features of their functioning in works of art and folklore, as well as in phraseological units.